Bortezomib, thalidomide, and dexamethasone with or without daratumumab before and after autologous stem-cell transplantation for newly diagnosed multiple myeloma (CASSIOPEIA): a randomised, open-label, phase 3 study. Issue 10192 (6th July 2019) - Moreau, Philippe; Attal, Michel; Hulin, Cyrille; Arnulf, Bertrand; Belhadj, Karim; Benboubker, Lotfi; Béné, Marie C; Broijl, Annemiek; Caillon, Hélène; Caillot, Denis; Corre, Jill; Delforge, Michel; et al.
Summary: Background: Bortezomib, thalidomide, and dexamethasone (VTd) plus autologous stem-cell transplantation is standard treatment in Europe for transplant-eligible patients with newly diagnosed multiple myeloma. We evaluated whether the addition of daratumumab to VTd before and after autologous stem-cell transplantation would improve stringent complete response rate in patients with newly diagnosed multiple myeloma. Methods: In this two-part, randomised, open-label, phase 3 CASSIOPEIA trial, we recruited transplant-eligible patients with newly diagnosed multiple myeloma at 111 European sites. Patients were randomly assigned (1:1) to receive four pre-transplant induction and two post-transplant consolidation cycles of VTd alone (VTd group) or in combination with daratumumab (D-VTd group). The primary endpoint of part 1 was stringent complete response assessed 100 days after transplantation. Part 2 (maintenance) is ongoing. The trial is registered withClinicalTrials.gov, numberNCT02541383 . Findings: Between Sept 22, 2015, and Aug 1, 2017, 1085 patients were enrolled at 111 European sites and were randomly assigned to the D-VTd group (n=543) or the VTd group (n=542). At day 100 after transplantation, 157 (29%) of 543 patients in the D-VTd group and 110 (20%) of 542 patients in the VTd group in the intention-to-treat population had achieved a stringent complete response (odds ratio 1·60, 95% CI 1·21–2·12, p=0·0010). 211 (39%) patients in the D-VTd group versus 141 (26%) in the VTd group achieved a complete response or better, and 346 (64%) of 543 versus 236 (44%) of 542 achieved minimal residual disease-negativity (10 −5 sensitivity threshold, assessed by multiparametric flow cytometry; both p<0·0001). Median progression-free survival from first randomisation was not reached in either group (hazard ratio 0·47, 95% CI 0·33–0·67, p<0·0001). 46 deaths on study were observed (14 vs 32, 0·43, 95% CI 0·23–0·80). The most common grade 3 or 4 adverse events were neutropenia (28% vs 15%), lymphopenia (17% vs 10%), and stomatitis (13% vs 16%). Interpretation: D-VTd before and after autologous stem-cell transplantation improved depth of response and progression-free survival with acceptable safety. CASSIOPEIA is the first study showing the clinical benefit of daratumumab plus standard of care in transplant-eligible patients with newly diagnosed multiple myeloma. Funding: The Intergroupe Francophone du Myélome and Dutch-Belgian Cooperative Trial Group for Hematology Oncology.